Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt \(A=\dfrac{3}{4}+\dfrac{8}{9}+...+\dfrac{9999}{10000}=1-\dfrac{1}{4}+1-\dfrac{1}{9}+...+1-\dfrac{1}{10000}\)
\(=99-\left(\dfrac{1}{2^2}+\dfrac{1}{3^2}+\dfrac{1}{4^2}+...+\dfrac{1}{100^2}\right)=99-B\)
Do \(B=\dfrac{1}{2^2}+\dfrac{1}{3^2}+...+\dfrac{1}{100^2}>0\Rightarrow99-B< 99\Rightarrow A< 99\)
Do \(B=\dfrac{1}{2^2}+\dfrac{1}{3^2}+...+\dfrac{1}{100^2}< \dfrac{1}{1.2}+\dfrac{1}{2.3}+...+\dfrac{1}{99.100}\)
\(\Rightarrow B< \dfrac{1}{1}-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{3}+...+\dfrac{1}{99}-\dfrac{1}{100}=1-\dfrac{1}{100}\)
\(\Rightarrow A=99-B>99-\left(1-\dfrac{1}{100}\right)=98+\dfrac{1}{100}>98\)
Vậy \(98< \dfrac{3}{4}+\dfrac{8}{9}+...+\dfrac{9999}{10000}< 99\)
\(p=\left[\left(x+5\right).\left(x+11\right)\right].\left[\left(x+7\right).\left(x+9\right)\right]+16=\)
\(=\left(x^2+16x+55\right)\left(x^2+16x+63\right)+16=\)
\(=\left(x^2+16x\right)^2+118.\left(x^2+16x\right)+3481=\)
\(=\left(x^2+16x\right)^2+2.\left(x^2+16x\right).59+59^2=\)
\(=\left[\left(x^2+16x\right)+59\right]^2\) là một số chính phương
\(\frac{\left[35\left(27^2+2.9^{11}\right)\right]}{\left[15\left(8^{16}-12.3^{19}\right)\right]}=5,2\)
a) Vì (-3) < (-2)
b) Vì -(3) < -(-9) {nhân với (-4)}
c) Vì (-3)>(-4)
Ta có: 9 > 8 => 916 > 816 = (23)16 = 248
Do đó: 916 > 248
Mặt khác: 1511 < 1611 = (24)11 = 244
Nên 1511 < 244
Do t/c bắc cầu: 916 > 248 > 244 > 1511
=> 916 > 1511
--> đpcm